1976
DOI: 10.1021/jm00226a003
|View full text |Cite
|
Sign up to set email alerts
|

Drugs derived from cannabinoids. 5. .DELTA.6a,10a,-Tetrahydrocannabinol and heterocyclic analogs containing aromatic side chains

Abstract: Ten new delta6a,10a-THC analogs with arylalkyl side chains, one with a dimethylaminoalkyl side chain, and six heterocyclic delta6a,10a-THC analogs [8-substituted 5,5-dimethyl-10-hydroxy-2-(2-propynyl)-1,2,3,4-tetrahydro-5H-[1]benzo-pyrano[4,3-c]pyridines] were prepared. They showed pharmacological activity as analgesics, tranquilizers, antihypertensives, and hypnotics and as antisecretory, antiulcer, and antidiarrheal agents. The most potent compounds had either a 1-methyl-4-(4-fluorophenyl)butyl or a 1,2-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the gastrointestinal tract, CB 1 receptors have been involved in the control of intestinal motility in different animal species (Heinemann et al ., 1999; Izzo et al ., 2000) and in humans (Croci et al ., 1998). Recently, cannabinoids have been found to reduce intestinal secretion (Tyler et al ., 2000) and to exert gastroprotective effects against the damage induced by stress (Germanò et al ., 2001), thus confirming previous data obtained with Δ 9 ‐tetrahydrocannabinol (Δ 9 ‐THC) in pylorus‐ligated rats (Winn et al ., 1976; Rivas‐V & Garcia, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In the gastrointestinal tract, CB 1 receptors have been involved in the control of intestinal motility in different animal species (Heinemann et al ., 1999; Izzo et al ., 2000) and in humans (Croci et al ., 1998). Recently, cannabinoids have been found to reduce intestinal secretion (Tyler et al ., 2000) and to exert gastroprotective effects against the damage induced by stress (Germanò et al ., 2001), thus confirming previous data obtained with Δ 9 ‐tetrahydrocannabinol (Δ 9 ‐THC) in pylorus‐ligated rats (Winn et al ., 1976; Rivas‐V & Garcia, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical firms and other entities are actively engaged in synthesizing analogs of the cannabinoids, (Pars et al 1976;Razdan and Dalzell 1976;Razdan et al 1976aRazdan et al , 1976bWinn et al 1976;Kurth et al, 1976), instead of further exploring uses of the natural parent compounds. Patent difficulties and stability problems of the natural derivatives as well as legal and political implications have no doubt played an important role in this decision.…”
Section: Monoterpenoid Chromenesmentioning
confidence: 99%
“…Indeed, the cannabinoid side chain, which is the focus of this study, has been known to be a key pharmacophore since Adams demonstrated the increased potency of the dimethylheptyl analogue of Δ 6a-10a -THC . More recent studies have further demonstrated the critical role played by side-chain length and conformation in determining pharmacological activity (see refs , −31 for examples). For example, in studies by Martin et al the substitution of the pentyl side chain of the inactive cannabinoid 11-nor,9-COOH-Δ 9 -THC with a dimethylheptyl side chain resulted in an active compound, approximately equipotent to Δ 9 -THC itself.…”
Section: Introductionmentioning
confidence: 99%